Mathematical analysis of Jeffrey ferrofluid on stretching surface with the Darcy–Forchheimer model - Saleem Musharafa; Hussain Majid; Haider Aun (Nonlinear Engineering)
The study examines the laminar two-dimensional flow with heat and mass transfer of Jeffrey fluid having thermal radiation and heat source–sink effects past a linearly inclined vertical stretched sheet under Stefan blowing. The impact of a magnetic dipole is also examined on two different thermal processes: prescribed surface temperature (PST) and prescribed heat flux (PHF). Furthermore, the Darcy–Forchheimer model, mixed convection, Buongiorno fluid model, and slip conditions are incorporated to enhance these thermal and concentration characteristics. With their unique combination of liquid and magnetic properties, ferromagnetic fluids are useful in a variety of scientific and industrial fields. The purpose of this study is to investigate how viscous dissipation, Soret and Dufour effects, and a magnetic dipole affect fluid flow, heat transfer, and concentration transfers in Jeffrey fluid over an inclined vertical stretching surface. For the concentration profile, the rheological model (a system of partial differential equations) incorporates partial slip effects, thermophoresis, and Brownian motion effects. Using similarity transformations, the model equations are transformed into coupled nonlinear ordinary differential equations. The BVP4C method is employed to obtain solutions to the fluid’s velocity, temperature, and concentration profiles. Various parameters are analyzed to determine their influence, with effects represented in tables and graphs for both PST and PHF thermal processes. Results for specific cases are compared with previously published results, showing good agreement. Thermal radiation increases the temperature for PHF processes, while the magnetic dipole reduces the fluid’s velocity and increases the temperature for PST.